Twenty years of experimental philosophy research. - Li, Jincai; Zhu, Xiaozhen (Metaphilosophy, 2023)
This paper reports the first study in the literature that adopts a bibliometric approach to systematically explore the scholarship in the young and fast‐growing research field of experimental philosophy. Based on a corpus of 1,248 publications in experimental philosophy from the past two decades retrieved from the PhilPapers website, the study examined the publication trend, the influential experimental philosophers, the impactful works, the popular publication venues, and the major research themes in this subarea of philosophy. It found, first, an overall growing trend in publications in experimental philosophy, encompassing four developmental stages. Second, it found that significant changes in topics of interest have taken place, with some gaining increasing attention, others seemingly going out of fashion, and still others remaining popular constantly. Third, the study identified lists of leading philosophers, frequently cited publications, and popular journals helpful for researchers and newcomers to get a quick start in learning about the field.